Compromised Ecosystem Services From Urban Aerial Microbiomes: A Review of Impacts on Human Immune Function - Flies, Emily J.; Jones, Penelope; Buettel, Jessie C.; Brook, Barry W. (Frontiers in Ecology and Evolution, 2020)
Biodiverse environments contribute to human health through a wide range of ecosystem services: from providing food and medicines to filtering our air and water. Exposure to biodiverse, airborne microbial communities (aerobiomes) contributes to the development of healthy human-immune function. This overlooked but potentially powerful ecosystem service is akin to nature’s provision of traditional medicines and pharmaceutical compounds. But urban environments appear to support less diverse aerobiomes, suppressing this ecosystem service and potentially contributing to urban-associated diseases through altered immune function. Here, we synthesize the known relationships between aerobiome biodiversity and health and present the experimentally demonstrated mechanisms that connect aerobiome exposure to immune function. We then summarize what is currently known about the effect of urbanisation on aerobiomes and identify several important knowledge gaps in this field, including a lack of rigorous, experimental, multi-scale studies demonstrating the mechanistic pathways between urbanization, altered aerobiomes and human health. We offer practical approaches that can close these knowledge gaps and will facilitate the transfer of knowledge and technology between microbiologists, urban ecologists and public-health practitioners. This synthesis should stimulate interdisciplinary research efforts to advance our understanding of how urbanisation is impacting aerobiome ecosystem services, and what that means for human health.